Oligomeric Proanthocyanidins: An Updated Review of Their Natural Sources, Synthesis, and Potentials - Fanxuan Nie; Lili Liu; Jiamin Cui; Yuquan Zhao; Dawei Zhang; Dinggang Zhou; Jinfeng Wu; Bao Li; Tonghua Wang; Mei Li; Mingli Yan (MDPI AG, 2023)
Oligomeric Proanthocyanidins (OPCs), as a class of compounds widely found in plants, are particularly abundant in grapes and blueberries. It is a polymer comprising many different monomers, such as catechins and epicatechins. The monomers are usually linked to each other by two types of links, A-linkages (C-O-C) and B-linkages (C-C), to form the polymers. Numerous studies have shown that compared to high polymeric procyanidins, OPCs exhibit antioxidant properties due to the presence of multiple hydroxyl groups. This review describes the molecular structure and natural source of OPCs, their general synthesis pathway in plants, their antioxidant capacity, and potential applications, especially the anti-inflammatory, anti-aging, cardiovascular disease prevention, and antineoplastic functions. Currently, OPCs have attracted much attention, being non-toxic and natural antioxidants of plant origin that scavenge free radicals from the human body. This review would provide some references for further research on the biological functions of OPCs and their application in various fields.